THE INFLUENCE OF STAKEHOLDERS MANAGEMENT ON TRUST IN CONSTRUCTION PROJECTS - Sukindrawati, Buddewi (Institut Teknologi Nasional Yogyakarta, 2025)
Stakeholders are groups or individuals who can influence or be influenced by the achievement of organizational goals. Stakeholder management is identified as the process by which the project team manages stakeholder needs and ensures their goals are achieved. The purpose of this study is to examine factors that influence stakeholder management on trust in construction projects that have an impact on project success. The research method used is a quantitative method with a total of 124 respondents in contracting companies in the Yogyakarta Special Region. The analytical method used is multiple linear regression analysis with the help of a computer program data processing tool SPSS 25.0.. The results of the research on the factors that influence stakeholder management on trust in construction projects are prescriptive stakeholders management (X1), intuitive trust (X2), competence trust (X4), honesty (X5), integrity trust (X3), and communication (X6). The result of the analysis states that the most dominant variable which significantly influences the prescriptive stakeholder management (X1), hence it is important for stakeholders mapping, identification, classification, and monitoring from the start of the project